2003
DOI: 10.1074/jbc.m307567200
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone Rapidly Stimulates Hyaluronan Synthesis by Periosteal Osteoblasts in the Tibial Diaphysis of the Growing Rat

Abstract: Short term treatment (3-24 h) with parathyroid hormone (PTH) stimulated the synthesis and accumulation of hyaluronan (HyA) in explant cultures of tibial diaphyses from young rats. PTH increased the overall HyA content of periosteum 5-fold, with the basal cambium layer exhibiting the greatest enhancement (ϳ8-fold). PTH increased the HyA content of cortical bone by 2-fold while not affecting the HyA content of bone marrow. PTH treatment greatly enhanced HyA staining throughout all layers of the periosteum, altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 43 publications
(44 reference statements)
2
35
0
Order By: Relevance
“…Likewise, it has been reported that PTH (1-34) stimulates HA synthesis in calvarial explants, periosteal rat osteoblasts, and osteoblast-like rat cell lines (16,17) whereas, the effects of PTH (7-84) on osteoblastic cell HA metabolism have not been addressed so far. It is worthwhile to note that these previous reports had established a correlation between the effects of PTH (1-34) on osteoblastic lineage cell HA metabolism and differentiation status (16,17). In the present study, the effects of PTH (1-34) on HA metabolism were strongly dependent on the administration mode and the differentiation of the osteosarcoma cells, in accordance with previous findings (16,17).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Likewise, it has been reported that PTH (1-34) stimulates HA synthesis in calvarial explants, periosteal rat osteoblasts, and osteoblast-like rat cell lines (16,17) whereas, the effects of PTH (7-84) on osteoblastic cell HA metabolism have not been addressed so far. It is worthwhile to note that these previous reports had established a correlation between the effects of PTH (1-34) on osteoblastic lineage cell HA metabolism and differentiation status (16,17). In the present study, the effects of PTH (1-34) on HA metabolism were strongly dependent on the administration mode and the differentiation of the osteosarcoma cells, in accordance with previous findings (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…It is worthwhile to note that these previous reports had established a correlation between the effects of PTH (1-34) on osteoblastic lineage cell HA metabolism and differentiation status (16,17). In the present study, the effects of PTH (1-34) on HA metabolism were strongly dependent on the administration mode and the differentiation of the osteosarcoma cells, in accordance with previous findings (16,17). Thus, intermittent treatment with PTH (1-34) increased the synthesis of HA and its' deposition in the pericellular matrix of MG-63 cells by stimulating their HAS2 expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of ligament and tendon muscle attachments, and fibrocartilage, on some areas of the periosteal surface means that periosteal cells are exposed to the different physical environments in contrast to more frequently studied endosteal cells, which are bathed in hematopoietic marrow. Compared to endosteal osteoblasts, periosteal osteoblasts exhibit greater mechanosensitivity to strain, 61 a lower threshold of responsiveness to parathyroid hormone, 82 higher levels of expression of proteins such as periostin 55,90,123 and more estrogen α receptors. 21 These differences in threshold sensitivity to physical, hormonal, and mechanical stimuli may underlie the differences in periosteal and endosteal surface responses to therapy.…”
Section: Microscopic Featuresmentioning
confidence: 99%